Effect of Interactive Media on Fifth Graders’ Learning Motivation at SDN 9 Ampenan - Alfarizi Alfarizi; Ida Ermiana; Aisa Nikmah Rahmatih (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Instructional media serve a pivotal function in facilitating the achievement of learning objectives. The integration of interactive learning media represents a significant innovation within the educational landscape, particularly in fostering enhanced learning motivation, encouraging students to engage more actively in the learning process. This study examines how interactive media influence fifth-grade students' learning motivation at SDN 9 Ampenan. Employing a quantitative approach with a quasi-experimental method, the research utilized a nonequivalent control group design. The population consisted of all fifth-grade students, with the sample comprising class Va (31 students) as the experimental group and class Vc (29 students) as the control group. Data were collected using a structured student motivation questionnaire. The results, analyzed using an independent sample t-test, revealed a calculated t-value of 8.061, which exceeds the critical t-value of 1.988 at a 5% significance level (α = 0.025), with a p-value of 0.001 < 0.05, indicating statistical significance. These findings suggest that the application of interactive media exerts a significant positive effect on the learning motivation of fifth-grade students at SDN 9 Ampenan.